2013
DOI: 10.1167/iovs.12-11173
|View full text |Cite
|
Sign up to set email alerts
|

Correlation Between the Ganglion Cell-Inner Plexiform Layer Thickness Measured With Cirrus HD-OCT and Macular Visual Field Sensitivity Measured With Microperimetry

Abstract: GCA thickness measured by Cirrus HD-OCT showed statistically significant structure-function associations with central VF. Inferotemporal central VF had the strongest association.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
69
0
7

Year Published

2013
2013
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 85 publications
(80 citation statements)
references
References 24 publications
4
69
0
7
Order By: Relevance
“…The reason for this location-dependent effect may be that the displacement of the macular GCs from the corresponding cones is maximal closest to the fovea 3 8 9. A previous study similarly reported that inferotemporal GC/IPL thickness had the highest correlation with corresponding sensitivities on microperimetry superotemporally 23. But, the correlation with and without correction for RGC displacement was not compared in that study 23…”
Section: Discussionmentioning
confidence: 79%
“…The reason for this location-dependent effect may be that the displacement of the macular GCs from the corresponding cones is maximal closest to the fovea 3 8 9. A previous study similarly reported that inferotemporal GC/IPL thickness had the highest correlation with corresponding sensitivities on microperimetry superotemporally 23. But, the correlation with and without correction for RGC displacement was not compared in that study 23…”
Section: Discussionmentioning
confidence: 79%
“…[21][22][23][24] Approximately half of the retinal ganglion cells are concentrated in the macula; thus, measurement of these large cell bodies in the macular ganglion cell complex has proven useful for the early detection of glaucoma and for monitoring changes in the optic nerve or assessing retinal diseases. 6,[9][10][11] Repeatability, which is used to verify the accuracy and reliability of a value, is the variability in the measurements obtained by 1 person using the same tool and method for measuring the same item repeatedly. 25 Liu and associates 26 reported high repeatability in normal eyes following repeated measurements of thickness in the 8 layers of the macula using SD OCT, and Pinilla and associates 27 found high repeatability of macular thickness measurements using TD OCT and SD OCT in normal eyes and eyes with epiretinal membrane.…”
Section: Discussionmentioning
confidence: 99%
“…7,8 Recently, as interest in the ganglion cell-inner plexiform layer has grown, SD OCT has been found to be useful for the investigation of glaucoma and optic nerve and macular diseases. 6,[9][10][11][12][13][14][15][16] The ganglion cell-inner plexiform layer thickness can be measured directly using a manual method or automatically using auto-segmentation to measure the thickness of each layer of the OCT images. 17 Auto-segmentation may be affected by retinal elevation or atrophy, and the repeatability also could be affected.…”
mentioning
confidence: 99%
“…The GCC analysis algorithm was used to automatically measure the macular GCA thickness. 10 Software version 6.0 of the GCA algorithm (Carl Zeiss Meditec) was used to process the data and detects and measures macular GCIPL thickness within a 6 × 6 × 2 mm cube centered on the fovea. The following macular GCIPL thickness measurements were analyzed: average, minimum, and sectoral (superonasal, superior, superotemporal, inferotemporal, inferior, and inferonasal).…”
Section: Sd-octmentioning
confidence: 99%